2019
DOI: 10.1038/s41467-019-12108-6
|View full text |Cite
|
Sign up to set email alerts
|

The CXCL5/CXCR2 axis is sufficient to promote breast cancer colonization during bone metastasis

Abstract: Bone is one of the most common sites for metastasis across cancers. Cancer cells that travel through the vasculature and invade new tissues can remain in a non-proliferative dormant state for years before colonizing the metastatic site. Switching from dormancy to colonization is the rate-limiting step of bone metastasis. Here we develop an ex vivo co-culture method to grow cancer cells in mouse bones to assess cancer cell proliferation using healthy or cancer-primed bones. Profiling soluble factors from condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
75
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(85 citation statements)
references
References 73 publications
(81 reference statements)
3
75
0
1
Order By: Relevance
“…Second, the CXCL5-CXCR2 axis has also been associated with the process by which circulating tumour cells home to the bone 39 . In addition, a more recent study showed its importance in colonization during bone metastasis 84 . In line with these studies, we observed fewer cancer cells in the BM after inhibition of CXCR2 in both LD and JL conditions, and a lower degree of metastasis in JL condition (but not in the LD group), but it remains unclear which one of these mechanisms (or both) might be responsible.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the CXCL5-CXCR2 axis has also been associated with the process by which circulating tumour cells home to the bone 39 . In addition, a more recent study showed its importance in colonization during bone metastasis 84 . In line with these studies, we observed fewer cancer cells in the BM after inhibition of CXCR2 in both LD and JL conditions, and a lower degree of metastasis in JL condition (but not in the LD group), but it remains unclear which one of these mechanisms (or both) might be responsible.…”
Section: Discussionmentioning
confidence: 99%
“…It is additionally interesting to note that 14/18 of the upregulated protein-validated factors are associated with poor prognosis or invasion in breast cancers, when measured in serum or tissue; this suggests that cells which secrete these factors would have a negative impact on prognosis 39,48,57,58,64,[66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82] . It is also of interest to note that in these studies 8/14 of these poorprognostic factors have been seen to derive predominantly from stromal cells.…”
Section: Discussionmentioning
confidence: 99%
“…So, together, these data could explain the difference in terms of results with our study. Finally, a third study from Romero-Moreno et al [26] used another Ab (ab14935) mainly to stain mouse tissue. They report also a staining of bone and marrow cells from a human femoral head, but the nature of the cells expressing CXCR2 was not precise.…”
Section: Discussionmentioning
confidence: 99%